Preparing Undergraduate Students for Person-Centered Care: Longitudinal Effects of Intentional Teaching Strategies Over Time. - Masters, Christi; Gritt, Anne; Jaiswal, Aparajita; Krishnan, Lata (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: While there is an increasing body of evidence demonstrating the impact of intercultural learning (ICL) activities in preprofessional programs through varied pedagogical approaches, there is limited information about long-term outcomes of these approaches. The purpose of this study is to evaluate longitudinal outcomes of undergraduate students enrolled in speech-language pathology and audiology courses that embed intentional and structured ICL activities in their syllabi. Method: Participants (n = 50) were undergraduate students enrolled in at least two of four possible speech, language, and hearing sciences courses that embedded ICL activities. All courses had multiple ICL activities throughout the semester and required critical reflection papers after each ICL activity and a final reflection paper at the end of the semester. Using a mixed-methods approach, quantitative data using the Intercultural Development Inventory (IDI) and qualitative data from reflection papers were obtained from each participant. Results: Quantitative findings indicated that group IDI developmental orientation scores that increased after the first course with embedded ICL activities were maintained at the start of the final course incorporating ICL. Additionally, the group had another significant increase in developmental orientation scores after the final course. These quantitative findings were supported by themes that resulted from analysis of the qualitative reflections from students. Conclusions: The results of this study showed that structured ICL activities embedded throughout multiple courses facilitated lasting intercultural growth among undergraduate students. This study affirmed the value of intentional, longitudinal curricular design in order to prepare future clinicians and professionals to provide patient-centered care and to work effectively in diverse contexts.